Extended tumour necrosis factor/HLA-DR haplotypes and asthma in an Australian population sample. - Moffatt,MF; James,A; Ryan,G; Musk,AW; Cookson,WO (Thorax, 1999)
BACKGROUND: Tumour necrosis factor (TNF) is a potent pro-inflammatory cytokine which is prominent in asthmatic airways. TNF shows genetic variations in secretion which are linked to polymorphisms in the TNF gene complex and the surrounding major histocompatibility (MHC) locus. These polymorphisms do not seem to be themselves functionally important. In these circumstances, the identification of disease associated haplotypes (combination of alleles on individual chromosomes) may narrow the search for polymorphisms which alter gene function. METHODS: TNF-308, LTalpha NcoI, and HLA-DRB1 polymorphisms were investigated for association with asthma, bronchial responsiveness, and medication use in 1004 subjects in 230 families from a general population sample. RESULTS: The common LTalpha NcoI1/TNF-3082/HLA-DRB103 haplotype, which was present in 11% of unrelated individuals, was weakly associated with asthma (OR = 1.38, p = 0.016, corrected for familial correlation). The rarer LTalpha NcoI1/TNF-3082/HLA-DRB102 haplotype, which was found in 0.6% of unrelated subjects, was more strongly associated with asthma (OR = 6.68, p = 0.002). This haplotype also showed association with bronchial hyperresponsiveness (OR = 21.9, p = 0. 0000) and the use of inhaled or oral steroids (OR 8.0, p = 0.04). CONCLUSIONS: The results of this study show only two extended TNF/HLA-DR haplotypes to be associated with asthma. The search for functional alleles responsible for an increased risk of asthma should concentrate on the LTalpha NcoI1/TNF-3082/HLA-DRB102 haplotype.